REALIZATION OF INTEGRATED LEARNING IN STUDY PRACTICE: PRE-SERVICE TEACHERS EXPERIENCES - Briška, Ilze; Siliņa-Jasjukeviča, Gunta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The integrated teaching is important tool for promoting the development of students’ critical and creative thinking, self-cognition, learning and cooperation skills and cultural understanding in a constantly changing world. In Latvia, integrated curriculum has become a challenge for educational reforms, too. Latvian teacher educators are looking for appropriate Curriculum content and strategies, in order to promote pre-service teachers with understanding of integrated learning, courage and ability to implement them in professional activities. The aim of an article is analyze possibilities how to improve the pre-service teachers’ readiness to plan integrated lessons for study practice. Methods: qualitative analysis of students’ pedagogical practice diaries.In conclusions and discussion, the suggestions for the development of teacher education Curriculum towards strengthening the different approaches to integrated learning in school education.